A Protein from Dioscorea polystachya (Chinese Yam) Improves Hydrocortisone-Induced Testicular Dysfunction by Alleviating Leydig Cell Injury via Upregulation of the Nrf2 Pathway. (30th November 2021) - Yu, Shiting; Han, Bing; Xing, Xin; Li, Yixuan; Zhao, Daqing; Liu, Meichen; Wang, Siming
Abstract : Leydig cell injury has been described as a primary driver of testicular dysfunction and is affected by oxidative stress. Dioscorea polystachya (Chinese yam) is used to improve testicular dysfunction in clinical and pharmacological research via its antioxidative activity, but the mechanisms underlying the beneficial effect of Chinese yam on testicular dysfunction and its suppression of Leydig cell oxidative damage remain unclear. In this study, we obtained a Chinese yam protein (DP1) and explored its effectiveness and possible mechanism in improving testicular dysfunction in vivo and in vitro. We established a testicular dysfunction model in rats using hydrocortisone (HCT). DP1 increased body weight and organ index, improved the deterioration in testicular morphology (including increasing the diameter of seminiferous tubules and thickness of germinal cell layers, inhibiting testicular cell apoptosis by increasing the Bcl-2/Bax ratio, and impeding collagen leakage by downregulating TGF- β 1 and p-SMAD2/3 expression), and restored the testosterone content. In addition, DP1 enhanced the number of Leydig cells in rats and H2 O2 -induced TM3 Leydig cells, and the effect of DP1 on the apoptosis, fibrosis, and testosterone content of TM3 cells was similar to that observed in vivo. These changes were dependent on the regulation of oxidative stress, including significantly reduced intracellular 8-hydroxy-2-deoxyguanosine levels, enhanced superoxide dismutase activities, and decreased superoxide anion levels, which were confirmed via a superoxide overexpression system. Furthermore, we observed that DP1 promoted Nrf2 nuclear import and upregulated antioxidant factor expression in vivo and in vitro. However, Nrf2 silencing eliminated the ability of DP1 to increase the Bcl-2/Bax ratio, reduce the expression levels of TGF- β 1 and p-SMAD2/3, and increase testosterone contents in H2 O2 -induced TM3 cells. In conclusion, DP1 reversed the HCT-induced testicular apoptosis and fibrosis and decreased testosterone contents by alleviating Leydig cell oxidative damage via upregulation of the Nrf2 pathway.